Factor 11 single-nucleotide variants in women with heavy menstrual bleeding - Sophie Wiewel-Verschueren; André B. Mulder; Karina Meijer; René Mulder (Taylor & Francis Group, 2017)
In a previous study it was shown that lower factor XI (FXI) levels in women with heavy menstrual bleeding (HMB). Our aim was to determine the single-nucleotide variants (SNVs) in the F11 gene in women with HMB. In addition, an extensive literature search was performed to determine the clinical significance of each SNV. Patients referred for HMB (PBAC-score >100) were included. With direct sequencing analysis of all 15 exons and flanking introns of the F11 gene, 29 different non-structural SNVs were detected in 49 patients with HMB. Interestingly, most of these SNVs have previously been associated with venous thrombosis instead of bleeding. These findings have not helped to elucidate the molecular basis of HMB. They also question the specificity of previously reported F11 variations in patients with thrombosis. More studies are needed to explain the lower FXI levels seen in patients with HMB.IMPACT STATEMENTWomen with mild deficiencies of factor XI (FXI) (< 70%) are prone to excessive bleeding during menstruation. Bleeding manifestations are not well correlated with plasma FXI levels and bleeding episodes can vary widely among patients with similar low FXI levels. In a previous study we showed that women with heavy menstrual bleeding (HMB) had normal, but on average, lower levels of FXI than controls.In light of these findings, we performed F11 gene analysis to determine the single-nucleotide variants (SNVs) in women with HMB and performed an extensive literature search to determine the clinical significance of each SNV. By direct sequencing analysis of the F11 gene we found 29 different non-structural SNVs in 49 women with heavy menstrual bleeding. Remarkably, a number of these SNVs have previously been implicated in thrombosis.These findings have not helped to elucidate the molecular basis of lower FXI levels in HMB. They also question the specificity of previously reported F11 variations in patients with thrombosis. More studies are needed to explain the lower FXI levels seen in patients with HMB.